Characterization of Geochemical and Isotopic Profiles in the Southern Zone Geothermal Systems of Mount Seulawah Agam, Aceh Province, Indonesia - Lala, Andi; Yusuf, Muhammad; Suhendra, Rivansyah; Maulydia, Nur Balqis; Dharma, Dian Budi; Saiful, Saiful; Idroes, Rinaldi (Heca Sentra Analitika, 2024)
The Seulawah Agam geothermal area exhibits significant potential as a source of energy for power generation, with an estimated capacity of 130 MW. Geological and geochemical investigations indicate that the Seulawah Agam geothermal system is part of the extensive Sumatra Fault. Analysis of the geochemical composition of geothermal water at the South Zone manifestation location of Mount Seulawah Agam, Aceh Province-Indonesia, involves examining cation (K+, Na+, Ca2+, and Mg2+), anion (Cl-, HCO3-, and SO42-), and isotope (δD and δ18O) contents. This data aids in estimating reservoir temperatures using geothermometer equations. Surface characteristics of the South Zone manifestation reveal neutral to alkaline pH values (6.02 to 8.68), relative temperatures (29.97 to 42.57 ºC), conductivity (49.8 to 100.7 mV), and TDS (Total Dissolved Solids) ranging from 352.6 to 497.0 mg/L. The dominant water composition is sodium–calcium–bicarbonate (Ca–Na–HCO3), indicating a bicarbonate water type. Average temperature depths in the South Zone manifestation of Mount Seulawah Agam are estimated as follows: Alue Ie Seu’um around 288.84 ± 2.19 ºC, Alue Ie Masam around 304.17 ± 20.9 ºC, Alue PU around 290.02 ± 6.85ºC, and Alue Teungku around 265±11.39 ºC. Isotope data (δD and δ18O) suggest meteoric water as the source for this manifestation. Fluid geochemical analysis indicates the potential for utilizing the geothermal manifestations of the South Zone of Mount Seulawah Agam for geothermal development or the construction of a geothermal power plant, given its high enthalpy system with an average temperature exceeding 225 ºC. Further research, including data drilling, is essential to gather precise subsurface data. Additionally, the Aceh Provincial Government should formulate policies to identify strategic areas for geothermal development, leveraging the existing exploitable potential.